Oncological Outcomes of Stage II Endometrial Cancer: A Retrospective Analysis of 250 Cases. Issue 1 (1st January 2018) - Ozgul, Nejat; Boyraz, Gokhan; Salman, Mehmet Coskun; Gultekin, Murat; Yuce, Kunter; Ibrahimov, Akbar; Erturk, Anil; Gungorduk, Kemal; Gulseren, Varol; Sanci, Muzaffer; Turkmen, Osman; Karalok, Alper; et al.
Abstract : Objective: The aim of this study was to investigate the effect of different surgical approaches, adjuvant therapy, and pathological characteristics on oncological outcomes in patients with 2009 International Federation of Gynecology and Obstetrics (FIGO) stage II endometrial cancer (EC). Methods: A multicenter, retrospective department database review was performed to identify patients with FIGO 2009 stage II EC who underwent surgical staging between 2002 and 2015 at 5 gynecologic oncology centers in Turkey. Results: Original pathology reports of 4867 patients who underwent surgical treatment for EC were analyzed. The study group consisted of 250 FIGO stage II patients. Of these patients, 203 (81.2%) had endometrioid and 47 (18.8%) had nonendometrioid histologic subtype of EC. Whereas 199 patients (79.6%) underwent type I hysterectomy, the remaining 51 patients (20.4%) underwent radical hysterectomy. Of the 250 patients, 208 patients (83.2%) had adjuvant therapy including radiotherapy (pelvic external beam radiotherapy and/or vaginal brachytherapy [VBT]) and/or platinum-based chemotherapy. Disease recurred in 29 patients (11.6%). The 5-year disease-free survival (DFS) and overall survival (OS) for the entire cohort were 82% and 85%, respectively. Multivariate analysis showed that only adjuvant treatment ( P = 0.001; hazard ratio, 4.02; 95% confidence interval, 1.72–9.36) was significantly associated with DFS. According to multivariate analysis, only age older than 60 years ( P = 0.01; hazard ratio, 3.03; 95% confidence interval, 1.3–7.04) was identified as an independent risk factor for OS. However, there were no differences in OS when evaluated by grade, histology, tumor size, type of hysterectomy, or adjuvant treatment. Conclusions: In stage II EC, adjuvant external beam radiotherapy ± VBT were associated with increased DFS but not OS. However, the benefit of VBT alone on DFS could not be demonstrated. Only age was an independent risk factor for OS. Type of hysterectomy and histologic subtype of the tumor for patients with uterus-confined disease improved neither DFS nor OS in our study group.